Gathering nanorings via Fe2+–bipyridine coordination. Issue 55 (11th June 2015) - Miao, Qingqing; Yin, Chunying; Xie, Maolin; Luo, Yufeng; Hai, Zijuan; Yuan, Qingpan; Jiang, Jun; Liang, Gaolin
Abstract : Fe 2+ –bipyridine coordination was used to assemble nanorings into supernanostructures. Abstract : Spontaneously precise organization of small structures into complex superstructures is ubiquitous and important in nature. But using small building blocks to mimic this process remains a challenge to scientists. Herein, we report the rational design of a bipyridine-derivative1 and applied it for the self-assembly of nanorings. The addition of Fe 2+ to the nanorings resulted in the assembly of the nanorings into supernanostructures via Fe 2+ –bipyridine coordination. HPLC, HR-ESI/MS, UV-vis, DLS, and TEM analyses clearly validated the intramolecular cyclization, self-assembly of the nanorings, and the additional self-assembly of the superstructures via Fe 2+ –bipyridine coordination. We envision our strategy to be a new approach of precisely assembling nanostructures of ring shape into more complex superstructures.